Efektivitas Penerapan Outdoor Activity Terhadap Perkembangan Kreativitas Menggambar Anak Di Taman Kanak-Kanak Khalifah Tarusan - Putri wanti, Anggia; Yeni, Indra (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
The aim of this research is to find out how much influence outdoor activity has on the development of children's drawing creativity at Khalifah Tarusan Kindergarten. This research uses a quantitative approach in the form of a quasi experiment. The population of this study was all children at the Khalifah Tarusan Kindergarten with a sample of 10 children in class B2 and 10 children in B3. The data collection technique uses a test in the form of 12 statement items. Data analysis techniques use normality tests, homogeneity tests, hypothesis tests, and effect size tests with the help of the SPSS 23 application with a significance level of 5% (0.05). The results of the research show that the implementation of outdoor activities has a significant influence compared to indoor and control classes through teacher demonstrations on the development of children's creativity at the Khalifah Tarusan Kindergarten. With a pre-test score of 217 in the experimental class and a post-test of 393, while the control class had a pre-test score of 184 and post-test 314. With a sig (2-tailed) score of 0.000 < 0.05.